Downstream Regulatory Network of MYBL2 Mediating Its Oncogenic Role in Melanoma - Zhong, Feiliang; Liu, Jia; Gao, Chang; Chen, Tingting; Li, Bo (Frontiers in Oncology, 2022)
The transcription factor MYBL2 is widely expressed in proliferating cells. Aberrant expression of MYBL2 contributes to tumor malignancy and is associated with poor patient prognosis. However, the downstream transcriptional network that mediates its oncogenic properties remains elusive. In the present study, we observed that MYBL2 was overexpressed in malignant and metastatic melanoma patient samples and that the high expression level of MYBL2 was significantly associated with poor prognosis. A loss-of-function study demonstrated that MYBL2 depletion significantly decreased cell proliferation and migration and prevented cell cycle progression. We also determined that MYBL2 promoted the formation of melanoma stem-like cell populations, indicating its potential as a therapeutic target for treating resistant melanoma. Mechanistically, we constructed an MYBL2 regulatory network in melanoma by integrating RNA-seq and ChIP-seq data. EPPK1, PDE3A, and FCGR2A were identified as three core target genes of MYBL2. Importantly, multivariate Cox regression and survival curve analysis revealed that PDE3A and EPPK1 were negatively correlated with melanoma patient survival; however, FCGR2A was positively correlated with patient survival. Overall, our findings elucidate a MYBL2 regulatory network related to cell proliferation and cancer development in melanoma, suggesting that MYBL2 may be potentially targeted for melanoma diagnosis and treatment.